1999
DOI: 10.1103/physrevb.59.14313
|View full text |Cite
|
Sign up to set email alerts
|

Physical analysis of the state- and rate-dependent friction law: Static friction

Abstract: We report the first part of an extensive study of friction at a multicontact interface between nominally flat bodies, rough on the micrometer scale, made of polymer glasses. Temperature is controlled between 20°C and the glass transitions of poly͑methyl metacrylate͒ and polystyrene. In this article, we focus on static friction force. The static friction threshold to macroscopic slip increases with the contact time. Increasing temperature is found to accelerate markedly the aging process. This effect is correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
196
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(217 citation statements)
references
References 30 publications
20
196
1
Order By: Relevance
“…In order to study the dependence of the static friction force on contact time t c prior to sliding, we follow a procedure proposed by Berthoud et al (1999) : the slider is first put in steady sliding at a velocity V ref during 10 seconds in order to renew the contact population. It is then stopped, remaining under tangential load for a resting time t c .…”
Section: (A) Static Frictionmentioning
confidence: 99%
“…In order to study the dependence of the static friction force on contact time t c prior to sliding, we follow a procedure proposed by Berthoud et al (1999) : the slider is first put in steady sliding at a velocity V ref during 10 seconds in order to renew the contact population. It is then stopped, remaining under tangential load for a resting time t c .…”
Section: (A) Static Frictionmentioning
confidence: 99%
“…These experiments span a vast range of lengths, and include studies at the atomic [14], lab [7,8,11,12,13], and geological scale [9,10]. Recent experiments by Ovarlez et al [6] using granular materials sliding against the interior wall of a piston showed clear rate dependence that was associated with aging effects of individual solid-friction contacts and with the force network.…”
mentioning
confidence: 99%
“…This was not always the case, and an interesting example of a major relaxation event is seen in one of these runs about 350 s after the stopping of shearing; thereafter, continued slow relaxation occurred. A key insight is that, while the micro-contacts between particles may be strengthening in time [8,11,15], the stress network as a whole is relaxing over very long time scales.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We propose a model where this enhanced blocking effect can be simply interpreted by an aging effect of the contacts at the side walls. Friction coefficients of solid on solid contacts are known to evolve logarithmically with waiting time t [18]: µ s (t) = µ 0 s +β s log(t). According to fig.2a, we observe no noticeable variation of F min with velocity, for given height and RH.…”
mentioning
confidence: 99%